Performance analysis and enhancement of multicarrier transmission systems - Zhang, Keli (2008)
To support high transmission rates with sufficient robustness to radio channel impairments such as frequency-selective multipath fading, multicarrier modulation (MCM) has emerged as an attractive transmission scheme. Two important realizations of MCM in use or in research today are orthogonal frequency division multiplexing (OFDM) and multicarrier code division multiple access (MC-CDMA). Their performance can be shown to be closely dependent on the frequency-domain fading characteristics of the radio transmission channel. In this project, we consider generalized fading channels that contain a mixture of Rayleigh and/or Rician paths with or without inter-path correlations, and derive the first- and second-order fading statistics for every subcarrier in the received OFDM signal.